Mapping of profile students’ metacognitive awareness in Yogyakarta, Indonesia - Moh Irma Sukarelawan; Sriyanto Sriyanto (Universitas Ahmad Dahlan, 2019)
This study aims to map the metacognitive awareness profile of students. Respondents involved were 198 students (24% male and 76% female) who were spread in Grade X and XI Science. Respondents were selected using convenience sampling techniques at SMAN 2 Bantul in 2018/2019 Academic Year. Students' metacognitive awareness data were collected using the Jr. MAI developed by Kim et al. Students' metacognitive awareness data were analyzed descriptively and quantitatively. Results showed that female were more dominant having metacognitive awareness than male students. Overall, students already have good metacognitive awareness in knowledge and regulation aspects. Students' metacognitive knowledge were dominant distributed in Good (class X) and Very Good (class XI) category. While the Students' metacognitive regulations were dominant distributed in the Good category (class X and XI). The results of this study are expected to be used as a teacher's reference in designing effective teaching strategies to improve student academic achievement.Keywords: metacognitive awareness, metacognitive mapping, metacognitive profile, metacognitive students